Oral Melanotic Hyperpigmentation (OMH) among HIV Seropositive Patients: A Clinical Study at the University College Hospital, Ibadan (2017)
BACKGROUND: Oral melanin hyperpigmentation (OMH) has been classified as a HIV associated condition which may present as a brown-black macule or patch of the oral mucosa in HIV seropositive patients. HIV-OMH may be idiopathic, drug- induced or due to adrenal insufficiency. This cross-sectional study was conducted to determine the prevalence of HIV- OMH among HIV seropositive patients attending the Infectious Disease Institute centre, UCH Ibadan. METHODOLOGY: Consecutive, consenting HIV seropositive patients attending PEPFAR clinic, UCH, Ibadan were enrolled. Data collected included age, gender, duration since diagnosis of HIV and commencement of HAART, history of smoking, any systemic disease, WHO staging of HIV, CD4 count, presence of OMH and site affected. Data analysis was done using SPSS version 15. RESULTS: The study group of 150 HIV sero-positive patients comprised 24 males (16%) and 126 females (84%). Out of all the patients seen, OMH was seen in 97 of them, majority reported not being aware of the condition, some noted it before being diagnosed of HIV, while only 14(14.4%) reported the presence of OMH after being diagnosed with HIV and commencement of HAART (p= 0.032). Concerning the OMH sites, gingiva was most noted followed by tongue, palate, buccal and labial mucosa. CONCLUSION: The prevalence of HIV-OMH in this study was 14.4%. Gingiva was the most common site affected.